2005
DOI: 10.1002/mnfr.200500050
|View full text |Cite
|
Sign up to set email alerts
|

On the effects of graded levels of Fusarium toxin contaminated wheat in diets for gilts on feed intake, growth performance and metabolism of deoxynivalenol and zearalenone

Abstract: A total of 36 gilts (103 +/- 6 kg) were divided into four groups and fed diets with increasing proportions of a Fusarium toxin contaminated wheat over a period of 35 days. The concentrations of the indicator toxins deoxynivalenol (DON) and zearalenone (ZON) which were analyzed by HPLC methods were 210 and 4, 3070 and 88, 6100 and 235 and 9570 and 358 mug.kg(-1) diet fed to groups 1-4 respectively. Feed was partially refused during the first 21 days of the experiment by groups 2, 3 and 4 where two, three and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 27 publications
7
50
1
Order By: Relevance
“…Urine seems to be the main route of excretion of DON in ruminants; faecal and bilary excretion seems to be less important [2,6]]. However, it has been shown for pigs that the DON and DOM-1 concentration in bile increases with the DON intake [38]. In the current study, the DOM-1 concentrations in bile were linearly related to the DON intake (Fig.…”
Section: General Aspects Of Residues In Serum Milk and Bilementioning
confidence: 61%
“…Urine seems to be the main route of excretion of DON in ruminants; faecal and bilary excretion seems to be less important [2,6]]. However, it has been shown for pigs that the DON and DOM-1 concentration in bile increases with the DON intake [38]. In the current study, the DOM-1 concentrations in bile were linearly related to the DON intake (Fig.…”
Section: General Aspects Of Residues In Serum Milk and Bilementioning
confidence: 61%
“…Several authors showed that increasing DON-concentrations in feed may gradually reduce growth performance and feed intake of pigs Swamy et al 2003;Da¨nicke et al 2004cDa¨nicke et al , 2005, particularly in young pigs (Andretta et al 2012). Moreover, no significant difference in the serum:feed ratio of DON was found in piglets fed the DON'PC diet compared with those fed the control diet, suggesting that PC additive did not inactivate DON, but may decrease the adverse effects of DON through a reduction of the toxic effect of DON.…”
Section: Effects Of Don and Anti-mycotoxin Additives On Growth Performentioning
confidence: 99%
“…(1 feed) has been shown to induce anorexia, decrease weight gain and impair the immune system, resulting in an increased incidence of infectious diseases and digestive disorders (Rotter et al 1994;Do¨ll et al 2003;Swamy et al 2003;Da¨nicke et al 2004cDa¨nicke et al , 2005Da¨nicke et al , 2007Pinton et al 2008). Acute higher doses induce feed refusal, increased salivation, vomiting, hemorrhagic diarrhea and circulatory shock (Pestka and Smolinski 2005;Pinton et al 2008).…”
mentioning
confidence: 99%
“…Only bile and kidney contained detectable concentrations of DOM, the metabolite of DON while in trials incorporating higher concentrations of DON in the diets DOM could also be detected in muscle, liver, and serum [4,20].…”
Section: Discussionmentioning
confidence: 94%
“…The detection limit was 30 ng/g and the mean recovery was approximately 95%. Freeze-dried liver, kidney, muscle, bile, and serum samples were analyzed for DON and de-epoxy-DON (DOM) by HPLC with UV detection after incubation with b-glucuronidase (EC 3.2.1.31; Type H-2, Sigma -Aldrich Chemie, Taufkirchen, Germany) [4,11]. The detection limit was 4 ng/g for freeze-dried liver, kidney, and muscle and 4 ng/mL for bile and 2 ng/mL for serum with a mean recovery between 87 -95 and 86 -97% for DON and DOM, respectively.…”
Section: Analysesmentioning
confidence: 99%